Wiadomości . tygodnik NSZZ "Solidarność" Region Mazowsze, no. 113, 1984 ([s.n.], 1984)
Creation and circulation: Issue no. 2=52(1983) with imprint: for internal use, issue no. 3=53(1983) with caption: newsletter for internal use